Raman optical activity study of poly-L-proline chains of various lengths. Issue 3 (2010) - Profant Profant, V. V.; Šafařík Šafařík, M. M.; Bouř Bouř, P. P.; Baumruk Baumruk, V. V.
Abstract : Raman and Raman optical activity (ROA) spectra of several oligo- and poly-L-proline samples of various chain lengths were measured in a wide frequency range between 120 and 1800 cm −1 and analysed with respect to the main peptide chain conformation. Specifically, formation of polyproline II (PPII) helical conformation was studied in dependence on the increasing chain length N of the (L-proline)N sample. Due to high sensitivity of the ROA technique to the conformational stability and rigidity of peptide chain we were able to determine the characteristic spectral peaks associated with formation of stable PPII helical conformation in studied systems. The most relevant peaks are located at 405, 535 and 945 cm −1 . Additionally, based on our data analysis, we were able to determine the minimal length of (L-proline)N chain necessary for creation of the stable PPII conformation as N = 6.